PEER TO PEER LENDING DI INDONESIA DAN BEBERAPA PERMASALAHANNYA - Setiadi Saputra, Adi (Faculty of Law, Parahyangan Catholic University, 2019)
Peer to peer lending has developed into a new investment measure providing solution for middle and small business enterprises in Indonesia, i.e., to obtain loan without collateral. However, the business enterprise providing the platform for peer to peer lending (websites or other apps), connecting would be lenders and borrowers, almost always puts into the service agreement a disclaimer stating that it would not be held liable in case of default. Using a juridical dogmatic approach, the author discusses the existence of such disclaimers from the viewpoint of consumer protection. The main argument put forward here is that the business enterprise providing this service cannot and should not shy away from bearing responsibility in protecting the consumer, i.e. those that provide loans.